ANALISA POSTUR DAN MOOD PEKERJA PEMOTONGAN BEBEK DALAM PENINGKATAN PRODUKTIVITAS - Nugraheni, Diyah Dwi; Eka Apsari, Ayudyah; Widananto, Hardik (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2025)
Comfort at work is an important factor in the production process. By paying attention to comfort at work, it will reduce the complaints at work. Uncomfortable working places and conditions can cause losses and even accidents for employees. One of the consequences of a lack of comfort and safety in working conditions is musculoskeletal disorders. This study took place in one of the ducks cutting businesses located in Sidowayah Village, Klaten, Central Java. Workers in this business still show several less ergonomic working positions, this is indicated by the many complaints of fatigue and work-related diseases felt by workers. ith complaints from workers who show indications of work-related diseases occurring in the upper body, this problem can be solved by the Rapid Upper Limb Assessment (RULA) Method. In addition, the mood factor of the workers themselves also affects worker productivity, worker mood analysis is measured using the Profile of Mood States (POMS) Method. The results of the measurements showed that workers in this duck cutting business still need to improve their workstations. The posture values ​​obtained were 6, 4 and 5, indicating fatigue among the three workers with recommendations for improvement. Meanwhile, for the analysis of the mood of workers, it can be concluded that workers have different moods before and after work. The difference in mood shows results that are not too significant so that it can be interpreted that workers do not experience significant stress during work.